THE EFFECT OF TALENT MANAGEMENT AND KNOWLEDGE MANAGEMENT ON EMPLOYEE PERFORMANCE - Jaya, Umban Adi; Priyana, Indarta; Herlina, Elin; Gusyana, Dadang; Febriyanti, Intan Rike (JURNAL ILMIAH EDUNOMIKA, 2024)
A Likert-scale questionnaire was used to gather data from 100 randomly selected employees, and SPSS 25 was used to calculate path analysis, t test, f test, and coefficient of determination. The purpose of this research is to look at the impact of talent management and knowledge management on employee performance at PT Pampas Electric. This study's research strategy is descriptive verification using a quantitative approach. The results showed that the talent management variable (X1) had both good validity (all valid statement items) and excellent reliability (Alpha Cronbach score of 0.809). The knowledge management variable (X2) is highly valid and reliable (α = 0.839). Path analysis revealed a substantial positive impact of talent management (X1) on employee performance (β = 0.562, p < 0.05) and knowledge management (X2) on employee performance (Y) (β = 0.481, p < 0.05). These findings suggest that PT Pampas Electric's staff performance may be improved through effective talent management and knowledge management. The study concludes that talent and knowledge management play an important role in boosting employee performance. The practical implications of this research include the significance of firms successfully managing and developing personnel and knowledge in order to attain peak performance.